Molecular dynamics simulations for 5, 5′-bistetrazole-1, 1′-diolate (TKX-50) and its PBXs. Issue 24 (17th February 2016) - Yu, Yuehai; Chen, Shusen; Li, Xin; Zhu, Jiaping; Liang, Hui; Zhang, Xiaoxin; Shu, Qinghai
Abstract : Molecular dynamics has been carried out to study the mechanical properties, moldability, binding energies, and detonation properties of TKX-50 and TKX-50 based polymer bonded explosives (PBXs) with four commonly used polymer binders. Abstract : Molecular dynamics has been carried out to simulate the well-known new explosive compound 5, 5′-bistetrazole-1, 1′-diolate (TKX-50) and TKX-50 based polymer bonded explosives (PBXs) with four kinds of polymer binders, such as, fluorine (F2311 ), fluorine resin (F2641 ), polyethylene glycol (PEG) and ethylene-vinyl acetate copolymer (EVA). The isotropic mechanical properties (tensile modulus, bulk modulus, shear modulus and Poisson's ratio), moldability, and bonding energy are reported for first time for TKX-50 crystal and TKX-50 based PBXs. The mechanical properties of the explosive can be effectively raised by adding polymer binders in small amounts and the ability of different polymer binders improving the plasticity of TKX-50 in the increasing order PEG > EVA > F2641 = F2311 . The moldability of TKX-50 based PBXs is better than that of pure TKX-50, and the increasing order is PEG > EVA > F2311 > F2641 . The interaction between each of the crystalline surfaces and each of the polymers is different, the order of the abilities of different binders to combine TKX-50 crystal decreases as follows: F2311 > PEG ≈ F2641 > EVA. The calculated detonation performances for pure TKX-50 and TKX-50 based PBXs show that both of them are comparable with those of HMX. Ultimately, as for the four polymer binders, PEG is considered the best one for explosive TKX-50.